Response of citrus (Citrus sps.) rootstock hybrids to PEG induced drought under hydroponic system - KADAM, D M; DUBEY, A K; SHARMA, R M; MORADE, AMRUT; SHARMA, NIMISHA; BHARDWAJ, C (The Indian Journal of Agricultural Sciences, 2022)
Present study was carried out at the glasshouse facility of the ICAR-Indian Agricultural Research Institute, New Delhi during 2020–21 using a simple hydroponic platform to assess the polyethylene glycol (PEG) induced drought impact on shoot-root morphology and physio-biochemical traits of 4 newly developed citrus (Citrus sps.) rootstock hybrids. Hybrid CRH 21-13/14 displayed superior shoot morphological performance in drought, articulated in terms of increment in plant height (4.5%), leaf numbers (9.5%), and dry weight of shoot (7.0%) with the lowest leaf wilting index (LWI). A contrasting pattern was noticed in CRH 23-5/15, CRH 23-9/17 akin to sensitive check Jatti khatti. Hybrid CRH 21-13/14 exhibited extensively, ramified and improved root system, and was able to sustain root growth under drought. It also showed an increment in root tips (116.1%) and forks (12.6%) during drought, whereas the rest hybrids along with sensitive check (Jatti khatti) exhibited a declining trend. The strong positive association of most root traits with relative water content (RWC) and membrane stability index (MSI) underscored the contribution of root traits towards drought avoidance by optimizing water resources. Although all tested hybrids declined total chlorophyll, chlorophyll a/b ratio and CSI (chlorophyll stability index) to varying degrees during drought, CRH 21- 13/14 exhibited minimum decline. Study postulate superior drought tolerance of CRH 21-13/14 conferred by the drought avoidance mechanism and moderate performance of CRH 21-14/14 (Pummelo × Troyer) as against CRH 23-5/15 and CRH 23-9/17 (Pummelo × Morton hybrids).